2015
DOI: 10.1038/eye.2015.92
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal aflibercept for choroidal neovascularisation in angioid streaks

Abstract: Sir, Intravitreal aflibercept for choroidal neovascularisation in angioid streaksChoroidal neovascularisation (CNV) is a well-known complication of angioid streaks (AS). It affects 42-86% of patients and if untreated can result in significant vision loss. 1 Treatment options have included laser photocoagulation and photodynamic therapy; 1,2 with the advent of anti-vascular endothelial growth factor (VEGF) therapies, off-label anti-VEGF has become the treatment of choice and both bevacizumab and ranibizumab hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In 2 treatment-naïve patients, prompt intervention and administration of 1 and 3 IVIs of aflibercept (pro re nata) resulted in a favorable outcome that was maintained over a period of 12 and 9 months, respectively. 6 Administration of aflibercept in a treat-and-extend regimen resulted in complete restoration of BCVA in another treatment-naïve patient with early stage disease who received 6 IVIs of aflibercept over a period of 1 year. 7 Aflibercept has also been used as first line treatment in a recently published case of polypoidal choroidal vasculopathy secondary to AS.…”
Section: Discussionmentioning
confidence: 95%
“…In 2 treatment-naïve patients, prompt intervention and administration of 1 and 3 IVIs of aflibercept (pro re nata) resulted in a favorable outcome that was maintained over a period of 12 and 9 months, respectively. 6 Administration of aflibercept in a treat-and-extend regimen resulted in complete restoration of BCVA in another treatment-naïve patient with early stage disease who received 6 IVIs of aflibercept over a period of 1 year. 7 Aflibercept has also been used as first line treatment in a recently published case of polypoidal choroidal vasculopathy secondary to AS.…”
Section: Discussionmentioning
confidence: 95%
“…In 2006, the first favorable results for the treatment of CNV secondary to angioid streaks were achieved with bevacizumab [ 9 ]. Afterwards, several small studies about effectiveness of anti-VEGF in CNV secondary to angioid streaks were done with ranibizumab, bevacizumab, and aflibercept [ 17 , 22 27 ]. Recently, Sekfali et al concluded that switching from intravitreal ranibizumab to aflibercept represents a valid therapeutic option in patients with refractory or recurrent CNV secondary to angioid streaks [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large series of patients with AS-CNV followed up over 4 years, ranibizumab injections allowed stabilization of BCVA and suppression of angiographic leakage effectively [ 8 ]. Recently aflibercept has shown efficacy in treatment of both refractory and treatment naïve AS-CNV [ 9 , 13 , 14 ]. Aflibercept may offer an additional benefit over other anti-VEGF agents in terms of preventing CNV recurrence as it has a higher affinity for VEGF-A as well as the ability to bind VEGF-B and placental growth factor, resulting in a more effective inhibition of the pathological angiogenic process [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently aflibercept has shown efficacy in treatment of both refractory and treatment naïve AS-CNV [ 9 , 13 , 14 ]. Aflibercept may offer an additional benefit over other anti-VEGF agents in terms of preventing CNV recurrence as it has a higher affinity for VEGF-A as well as the ability to bind VEGF-B and placental growth factor, resulting in a more effective inhibition of the pathological angiogenic process [ 9 ]. Each patient received only 3 loading doses of anti-VEGF therapy (2 patients with ranibizumab and one with aflibercept) without further recurrences of AS-CNV till the last follow-up which was encouraging knowing the fact that CNV in AS has a high tendency of reactivation/recrudescence [ 8 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation